Analisis Laporan Keuangan Untuk Menilai Kinerja Keuangan Pada PT Fast Food Indonesia Tbk Tahun 2020-2023 - Karlina Nst, Lily; Husna, Asmaul; Manurung, Angie Fania (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
PT Fast Food Indonesia Tbk which operates in the fast food retail sector which is well known in Indonesia. PT Fast Food Indonesia Tbk has a negative company growth rate. The company still recorded a loss in the annual profit/loss report. Therefore, this research uses quantitative and descriptive methods to analyze the financial performance of PT Fast Food Indonesia Tbk in 2020-2023. The data collection method uses documentation and literature study methods, and the data used for this research is secondary data as a source of information. In this Financial Report Analysis, Profitability Ratios are measured using Return on Assets (ROA), Return on Equity (ROE), and Liquidity Ratios are measured using Current Ratio. PT Fast Food Indonesia Tbk has poor financial performance when viewed from the Liquidity ratio which is measured by the current ratio, the company does not have sufficient current assets to cover all its liabilities. The profitability ratio is not good and needs to be improved further to achieve a good level of performance